Association of egg intake with blood lipids, cardiovascular disease, and mortality in 177, 000 people in 50 countries. Issue 4 (21st January 2020) - Dehghan, Mahshid; Mente, Andrew; Rangarajan, Sumathy; Mohan, Viswanathan; Lear, Scott; Swaminathan, Sumathi; Wielgosz, Andreas; Seron, Pamela; Avezum, Alvaro; Lopez-Jaramillo, Patricio; Turbide, Ginette; Chifamba, Jephat; et al.
ABSTRACT: Background: Eggs are a rich source of essential nutrients, but they are also a source of dietary cholesterol. Therefore, some guidelines recommend limiting egg consumption. However, there is contradictory evidence on the impact of eggs on diseases, largely based on studies conducted in high-income countries. Objectives: Our aim was to assess the association of egg consumption with blood lipids, cardiovascular disease (CVD), and mortality in large global studies involving populations from low-, middle-, and high-income countries. Methods: We studied 146, 011 individuals from 21 countries in the Prospective Urban Rural Epidemiology (PURE) study. Egg consumption was recorded using country-specific validated FFQs. We also studied 31, 544 patients with vascular disease in 2 multinational prospective studies: ONTARGET (Ongoing Telmisartan Alone and in Combination with Ramipril Global End Point Trial) and TRANSCEND (Telmisartan Randomized Assessment Study in ACEI Intolerant Subjects with Cardiovascular Disease). We calculated HRs using multivariable Cox frailty models with random intercepts to account for clustering by study center separately within each study. Results: In the PURE study, we recorded 14, 700 composite events (8932 deaths and 8477 CVD events). In the PURE study, after excluding those with history of CVD, higher intake of egg (≥7 egg/wk compared with <1 egg/wk intake) was not significantly associated with blood lipids, composite outcome (HR: 0.96; 95% CI: 0.89, 1.04; P -trend = 0.74), total mortality (HR: 1.04; 95% CI: 0.94, 1.15; P -trend = 0.38), or major CVD (HR: 0.92; 95% CI: 0.83, 1.01; P -trend = 0.20). Similar results were observed in ONTARGET/TRANSCEND studies for composite outcome (HR 0.97; 95% CI: 0.76, 1.25; P -trend = 0.09), total mortality (HR: 0.88; 95% CI: 0.62, 1.24; P -trend = 0.55), and major CVD (HR: 0.97; 95% CI: 0.73, 1.29; P -trend = 0.12). Conclusions: In 3 large international prospective studies including ∼177, 000 individuals, 12, 701 deaths, and 13, 658 CVD events from 50 countries in 6 continents, we did not find significant associations between egg intake and blood lipids, mortality, or major CVD events. The ONTARGET and TRANSCEND trials were registered at clinicaltrials.gov as NCT00153101. The PURE trial was registered at clinicaltrials.gov as NCT03225586.